Sistem Pemberi Pakan Ayam Otomatis Berbasis IoT Dan Aplikasi Blink Sebagai Media Informasi - Wardini, Wardini; Aswandi, Aswandi; Indrawati, Indrawati (Politeknik Negeri Lhokseumawe, 2023)
manual chicken feed is considered less effective because it is often negligent to miss the specifiedtime. This automatic chicken feed is designed to make it easier for farmers to do their work. In general, theworking principle of the automatic chicken feed system is to provide automatic chicken feed 3 times, 7 am, 1pm, and 5.30 pm by using the RTC module (DS1307) as a schedule for chicken feed, filling drinking waterautomatically by utilizing sensors. ultrasonically to find out if the water tank is filled or empty when thewater and feed have run out, the chicken livestock officer can be notified from the blynk application via theESP8266 module which is integrated with wifi. The average response of the chicken feeding system is 0.33seconds, the percentage of success of the automatic feeder according to scheduled 90%.Kata kunci: Monitoring, IOT, Blynk